The effects of taxes and socioeconomic variables on market work and home production in Norway in the years 1970 to 2000 - Christoph Schwierz (University of Oslo, Department of Economics, 2003)
This paper analyses significant forces of the allocation of time to different home production activities, as developed by Gronau, in a data set consisting of decennial time-use surveys of Norwegian households. The theoretical framework consists of joint allocation of time model, where household decisions to allocate time between the market and the household are analyzed simultaneously. The estimation takes place within a limited dependent variables framework. As an alternative to the usually employed Tobit model, Craggs double-hurdle model is used, so as to be able to model individual decisions in a two step framework, discerning between the wish to participate and the amount of time to invest in different activities. The conclusion of the paper is that taxation has a significant effect on the allocation of time to market and non-market activities. There is evidence in favour of more disaggregation of time-use, but the overall message of the home production literature – that explicit consideration of the market-versus-home production margin can improve estimates of labor supply elasticities - is upheld.
Keywords: B21; D19; 330; home production; allocation of time; double-hurdle model; labor supply elasticities; Zeitallokation; Hausarbeit; Konsumtheorie; Mikroökonometrie; Norwegen